Evidence of direct estrogenic regulation of human corticotropin-releasing hormone gene expression. Potential implications for the sexual dimophism of the stress response and immune/inflammatory reaction. - Vamvakopoulos, N C (1993)
Corticotropin-releasing hormone (CRH) plays major roles in coordination of the stress response and regulation of the immune/inflammatory reaction, two important functions associated with sexual dimorphism. Two overlapping segments of the 5' flanking region of the human (h) CRH gene, the proximal 0.9 kb (containing two perfect half-palindromic estrogen-responsive elements [EREs]) and the 2.4 kb (including the former and containing two additional perfect half-palindromic EREs), were examined for their ability to confer estrogen-mediated transcriptional enhancement to a homologous or heterologous promoter. The level of estrogen-induced transactivation by the 0.9- and 2.4-kb segments was determined by chloramphenicol acetyltransferase analysis in CV-1 cells cotransfected with estrogen receptor (ER) cDNA expression plasmids, and found to be respectively approximately 10% and 20% of that of the strongly estrogen-responsive Xenopus vitellogenin A2 enhancer. Gel retardation and immunoprecipitation demonstrated specific association between the perfect half-palindromic EREs of hCRH gene and the DNA binding domain of hER in vitro. These findings may constitute the basis of sexual dimorphism in the expression of the CRH gene in the central nervous system and periphery, and might shed light in existing gender differences in stress response and immune regulation.